2010
DOI: 10.1136/emj.2009.087296
|View full text |Cite
|
Sign up to set email alerts
|

Rescue efforts management and characteristics of casualties of the Wenchuan earthquake in China

Abstract: The Wenchuan medical rescue effort presented several problems. The experience is reflected in these points: (1) establish an effective command and communication centre to ensure that medical rescue resources are deployed in time; (2) treat the wounded within the first 7 days; (3) prepare healthcare resources for both surgical and general medicine services; (4) establish contingency rescue plans with a coordinated effort; (5) insist on the principles of triage and adopt flexible evacuation and transfer methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…Currently, NHV operates in two counties which accounted for more than 20% of the earthquake casualties [22]. A comprehensive prospective evaluation of NHV effectiveness attributing program causal effects has not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, NHV operates in two counties which accounted for more than 20% of the earthquake casualties [22]. A comprehensive prospective evaluation of NHV effectiveness attributing program causal effects has not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…In China after the seventh day, acute upper-respiratory-tract infection was the leading problem (40). …”
Section: Resultsmentioning
confidence: 99%
“…From the view of injuries sustained and the patient spectrum after the earthquake, the comprehensive specialties of the AE medical staff met the treatment needs of the evacuated casualties. Previous medical rescue experiences during earthquakes have shown that, in addition to massive trauma caused by the earthquake, internal, gynecologic, and pediatric diseases began to increase within 3 -7 d after the earthquake ( 18 ). Medical staff included administrative personnel and information statisticians in addition to doctors, nurses, and anesthetists.…”
Section: Discussionmentioning
confidence: 99%